A Continuous-Flow Protocol for the Synthesis of Alkenyl Thioethers Based on the Photochemical Activation of Halogen-Bonding Complexes - Piedra, Helena F.; Valdés, Carlos; Plaza, Manuel (Synlett, 2024)
We report a useful flow protocol for the preparation of alkenyl thioethers from alkenyl bromides and thiols in basic media with visible-light irradiation. The reactions exhibit a wide functional-group tolerance, proceed under mild conditions, are stereoselective, and do not require the use of catalysts. The transformations can be successfully scaled up to 5 mmol scale without compromising the yield. The key to the success of these reactions is the photochemical excitation of halogen-bonding complexes to form alkenyl and sulfur-centered radicals, a protocol recently developed in our laboratories.
Keywords: photochemistry; flow chemistry; thioetherification; scale-up